2014
DOI: 10.1038/cdd.2014.129
|View full text |Cite
|
Sign up to set email alerts
|

L-GILZ binds p53 and MDM2 and suppresses tumor growth through p53 activation in human cancer cells

Abstract: The transcription factor p53 regulates the expression of genes crucial for biological processes such as cell proliferation, metabolism, cell repair, senescence and apoptosis. Activation of p53 also suppresses neoplastic transformations, thereby inhibiting the growth of mutated and/or damaged cells. p53-binding proteins, such as mouse double minute 2 homolog (MDM2), inhibit p53 activation and thus regulate p53-mediated stress responses. Here, we found that long glucocorticoid-induced leucine zipper (L-GILZ), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…It has been reported that TSC22D1 and TSC22D3 are significantly down-regulated in a wide variety of human tumors and act as tumor suppressor genes [5,[13][14][15][16][17][18][19][20]. Both of these genes inhibit cell proliferation and promote cellular apoptosis through the Ras/Raf signaling pathway and ubiquitin mediated-degradation of p53 [17][18][19][20]. T S C 2 2 D 3 a l s o e x a c t s a n t i -i n f l a m m a t o r y a n d Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TSC22D1 and TSC22D3 are significantly down-regulated in a wide variety of human tumors and act as tumor suppressor genes [5,[13][14][15][16][17][18][19][20]. Both of these genes inhibit cell proliferation and promote cellular apoptosis through the Ras/Raf signaling pathway and ubiquitin mediated-degradation of p53 [17][18][19][20]. T S C 2 2 D 3 a l s o e x a c t s a n t i -i n f l a m m a t o r y a n d Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Members of this family have diverse physiological functions, spreading from cell growth [5,6], development [7][8][9], and homeostasis [4] to immune regulation [10][11][12]. TSC22D1 and TSC22D3 are potential tumor suppressors and significantly down-regulated in a wide variety of human tumors [5,[13][14][15][16][17][18][19][20]. TSC22D2 may also anticipate the regulation of cell growth [8].…”
Section: Introductionmentioning
confidence: 99%
“…GILZ was recently independently identified as a key regulator of the Th17 program via binding to the promoters of Il21 and Irf4 and preventing binding of the positive regulators Stat3, RORgt, and Batf [15]. In addition to regulation of effector gene expression, GILZ regulates expression of genes involved in apoptosis (Bcl-X L [43]) and cell cycle entry (p21 and p53 [44]) and may exert an antiproliferative effect via modulation of these pathways in CD4 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…GILZ is a transcriptional regulator that binds DNA either as a homodimer, or as part of a heterodimeric complex with other transcriptional regulators including NF-κB and activator protein 1 (AP-1) 11–13. GILZ directly represses gene expression and has been reported to regulate expression of genes involved in apoptosis,14 cell cycle15 and inflammation 9 16–19. GILZ exerts a predominantly anti-inflammatory influence on T cells,18 20–22 macrophages23 and endothelial cells24 and we previously reported that in vivo silencing of GILZ exacerbates, while overexpression abrogates, autoimmune arthritis 9 25.…”
Section: Introductionmentioning
confidence: 99%